Tale of three services: early UK experience with mavacamten treatment for hypertrophic cardiomyopathy with left ventricular outflow tract obstruction - Jane Draper; Antonio De Marvao; Robert M Cooper; Gerry Carr-White; Nabeel Sheikh; Rachel Bastiaenen; Yande Kasolo; Jason N Dungu; Edward Burford (Open Heart)
Background Hypertrophic cardiomyopathy (HCM) is characterised by abnormal thickening of ventricular myocardium. Left ventricular outflow tract (LVOT) obstruction occurs in up to 70% of patients, causing progressive symptoms, heart failure and mortality. Mavacamten, the first targeted therapy for obstructive HCM (oHCM), was approved for use in the UK in 2024. We present data from the early experience with mavacamten treatment for oHCM in three UK centres and describe different clinical pathways.Methods All patients with symptomatic oHCM eligible for mavacamten therapy were included. Eligibility criteria included New York Heart Association (NYHA) class II–III symptoms and LVOT gradients >30 mm Hg with normal left ventricular ejection function (LVEF >55%), as per National Institute for Health and Care Excellence guidelines and product literature. Patients underwent CYP2C19 genotyping before treatment, and dosing was adjusted accordingly. Echocardiographic assessments, clinical reviews and biomarker analyses were conducted at weeks 0, 4, 8 and 12.Results 93 patients were initiated on mavacamten (mean age: 60±13 years; 72% male). The Valsalva LVOT gradient significantly decreased during treatment, from 88.9±31 mm Hg at baseline to 43.8±32.6 mm Hg by week 12, and further to 27.7±22.3 mm Hg on the maintenance dose. NT-proBNP levels also improved markedly, from 689 ng/L (IQR 343-1684 ng/L) at baseline to 171 ng/L (IQR 116-335 ng/L) on the maintenance dose. By week 12, 74% of patients experienced an improvement of at least one NYHA class, increasing to 91% on the maintenance dose. Temporary treatment interruptions occurred in 13 patients; however, no patients required permanent discontinuation of treatment due to a reduced LVEF (<50%). Outcomes were comparable across the three care pathways.Conclusions Mavacamten treatment was associated with significant symptomatic improvement, reduced LVOT gradients and improved biomarker profiles in patients with oHCM. The implementation of clinical services to deliver mavacamten in the UK should not follow a ‘one-size-fits-all’ approach but rather leverage the unique strengths of each specific centre.